Measuring the training external jump load of elite male volleyball players: an exploratory study in Portuguese League (Medición de la carga externa de entrenamiento de los jugadores de voleibol masculino de élite: un estudio exploratorio en la Liga Portug - Franco Lima, Ricardo; Palao, Jose; Castro, Henrique; Clemente, Filipe (Retos, 2019)
The purpose of this exploratory study was to assess the external jump-training load of different playing positions in male professional volleyball players during regular competitive microcycles. Five male elite volleyball players participated in this study. The sample was composed by five male elite volleyball players of a team from Portugal’s first division.was composed of 8,532 jumps were analyzed during 12 practice sessions of four competitive microcycles of the regular season (three practices in each microcycle). A descriptive design was implemented to analyze the number of jumps, jump heights, and rest time by players’ playing positions (middle blockers, setter, and outside hitters), by training sessions, and by microcycles. The jump height and jump moment were recorded using an inertial measurement device. The setter made a significantly greater number of jumps than middle blockers and outside hitters. Middle blockers and outside hitters accumulate their jumps in specific moments (frontcourt). No significant differences were found in the jump intensity with player positions and with different training days of the microcycle. Significant lower amount of jumps were found on the training day before the competition. Results show how the coach modified the jump-training load of the session in the day prior to the competition. Resumen. El propósito de este estudio exploratorio fue evaluar la carga externa de entrenamiento de salto de diferentes posiciones de juego en jugadores de voleibol profesionales masculinos durante microciclos competitivos regulares. Cinco jugadores masculinos de voleibol de élite participaron en este estudio. La muestra estuvo compuesta por cinco jugadores de voleibol de élite masculinos de un equipo de la primera división de Portugal. Se compuso de 8,532 saltos y se analizaron durante 12 sesiones de práctica de cuatro microciclos competitivos de la temporada regular (tres prácticas en cada microciclo). Se implementó un diseño descriptivo para analizar la cantidad de saltos, alturas de salto y tiempo de descanso por las posiciones de juego de los jugadores (bloqueadores medios, colocadores y bateadores externos), por sesiones de entrenamiento y por microciclos. La altura de salto y el momento de salto se registraron utilizando un dispositivo de medición inercial. Setter hizo un número significativamente mayor de saltos que los bloqueadores medios y los bateadores externos. Los bloqueadores medios y los bateadores externos acumulan sus saltos en momentos específicos primera línea. No se encontraron diferencias significativas en la intensidad del salto con las posiciones de los jugadores y con los diferentes días de entrenamiento del microciclo. Se encontró una cantidad de saltos significativamente menor en el día de entrenamiento antes de la competición. Los resultados muestran cómo el entrenador modificó la carga de entrenamiento de salto de la sesión en el día anterior a la competición.